Enhancing the flexibility of polyvinyl alcohol/Uncaria gambir extract/boric acid biopolymer films via prolonged water immersion post-treatment - Dieter Rahmadiawan; Hairul Abral; Shih-Chen Shi; Ilham Chayri Iby; Razan Muhammad Railis; Melbi Mahardika; Dian Juliadmi; Fazhar Akbar (Case Studies in Chemical and Environmental Engineering)
Polyvinyl alcohol (PVA) films mixed with boric acid (BA) and Uncaria gambir (UG) offer excellent UV shielding and moisture resistance but suffer from brittleness. This study introduces a water immersion technique to improve flexibility. The untreated film showed high tensile strength (57.7 MPa) and modulus (3.7 GPa) but low elongation (∼43 %) and toughness (20.2 MJ/m3). After 7 days of immersion, tensile strength and modulus decreased to 41.2 MPa and 1.94 GPa, while elongation and toughness increased to ∼150 % and 58.1 MJ/m3, respectively. This green approach effectively enhances the ductility of PVA-based biopolymer films.